Morpho-physiological responses of potato cultivars under weed competition - Franceschetti, Milena Barretta; Galon, Leandro; Toso, Janaíne Oliveira; Melo, Thaís Stradioto; Menegatti, André Dalpont; Concenco, Germani; Bagnara , Maico André Michelon; Perin, Gismael Francisco (Comunicata Scientiae, 2024)
Among the factors that affect potato productivity, the interference caused by weeds stands out as they may compete with the crop, release allelopathic substances to soil and host insects and diseases. Therefore, the objective of this work was to assess the competitive ability of white (Aghata) and pink (Asterix) potato cultivars when infested by Alexandergrass (Urochloa plantaginea) or wild poinsettia (Euphorbia heteroplylla). The experiment was carried out into greenhouse in randomized blocks design, with four replications. A single potato plant faced competition by either Alexandergrass or wild poinsettia, ranging from 0 to 64 plants per plot. Fifty days after seedling transplanting, variables related to the morphophysiology of potato cultivars and weeds were assessed. Potatoes have low competitive ability with both weed species, with wild poinsettia being the most aggressive in reducing the accumulation rates of leaf area and aboveground dry mass. Potato photosynthetic rate is negatively influenced by the presence of both weeds. Internal CO2 concentration, stomatal conductance, carboxylation efficiency and transpiration rates of potato varied depending on weed species and density. Morphological parameters are reduced when potato competed with Alexandergrass or wild poinsettia; however the physiological parameters are most sharply affected when under competition with wild poinsettia.